2001
DOI: 10.1046/j.1365-3024.2001.00361.x
|View full text |Cite
|
Sign up to set email alerts
|

A previous infection withToxoplasma gondiidoes not protect against a challenge withNeospora caninumin pregnant sheep

Abstract: Sheep immunized with Toxoplasma gondii (Toxovax) prior to pregnancy were tested for their ability to withstand a challenge at 90 days gestation with 107 Neospora caninum (NC1) tachyzoites. The antibody responses in sheep following immunization with T. gondii were specific for T. gondii whereas peripheral blood mononuclear cells responded to both T. gondii and N. caninum antigen in vitro. This suggested that there was induction of crossreactive immune recognition in the sheep, at least at the cellular level. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 26 publications
0
15
0
1
Order By: Relevance
“…Since T. gondii protective immunity in sheep involves cellular responses [23, 25], diluted whole blood samples collected three weeks after s.c. inoculation with 10 5 or 2 × 10 6 Mic1-3KO tachyzoites (Exp. 2), were exposed to T. gondii antigen in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Since T. gondii protective immunity in sheep involves cellular responses [23, 25], diluted whole blood samples collected three weeks after s.c. inoculation with 10 5 or 2 × 10 6 Mic1-3KO tachyzoites (Exp. 2), were exposed to T. gondii antigen in vitro (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro studies (Sunderman and Estridge, 1999) have demonstrated that Toxoplasma and Neospora can co-exist in tissue culture, and both species could invade the same host cell and undergo endodyogeny. Immunological studies (Innes et al 2001) showed that, although there was evidence of induction of cross-reactive immune recognition following immunization with T. gondii in sheep, this was not sufficient to prevent foetal loss following subsequent N. caninum oocyst challenge.…”
mentioning
confidence: 99%
“…In this study, we have demonstrated that heterologous immunization with an attenuated T. gondii strain induced protec- Previous studies have provided evidence of humoral and cellular cross-reactivity between T. gondii and N. caninum in different hosts (16,19,21,32), but the extent to which T. gondii immunization could protect against subsequent N. caninum infection has never before been investigated using the mouse model. Whereas in a pregnant-ruminant model of N. caninum infection, a T. gondii vaccinal strain failed to induce protection against N. caninum-induced abortion (16), mice infected with N. caninum were protected against lethal toxoplasmosis (19).…”
Section: Discussionmentioning
confidence: 85%
“…The heterologous protection induced by a commercial strain of T. gondii was previously studied by Innes et al using a ruminant model for congenital infection with N. caninum. This vaccination failed to protect against an N. caninum challenge at 90 days of gestation (16). The authors discuss the fact that under their challenge conditions, the immunity generated against the antigens common between T. gondii and N. caninum was insufficient to protect against fetal death, but if their challenge had been milder, it might allow detection of a biological effect.…”
Section: Discussionmentioning
confidence: 99%